Murder on Union Square - Thompson, Victoria (Victoria E.) (A Gaslight mystery, 2018)
"When a murder hits close to home, Frank finds himself in an unusual position--the prime suspect in the latest installment of the national bestselling Gaslight Mystery series... Frank and Sarah Malloy are enjoying married life and looking to make their family official by adopting Catherine, the child Sarah rescued and has been raising as her daughter. The newlyweds soon discover, Parnell Vaughn, an actor and Catherine's legal father, is looking to fatten his pockets by insisting on a financial settlement to relinquish his parental rights. Even though exchanging money for a child is illegal, Frank and Sarah's love for Catherine drives them to take a chance. When Frank returns with the money and finds Vaughn beaten to death, all evidence points to Frank as the culprit. A relatively unsuccessful actor with no money and little promise, Vaughn seems at first to be an unlikely candidate for murder--particularly such a violent crime of passion--but Frank soon uncovers backstage intrigue as dramatic as any that appears on stage. Sarah and Frank must use all of their resources to investigate Vaughn's death as Frank's own life hangs in the balance"--